Proton Pump Inhibitor–Associated Hypomagnesemia: What Do FDA Data Tell Us? - Luk, Chee; Parsons, Richard; Lee, Ya Ping; Hughes, Jeffrey (Harvey Whitney Books, 2013)
BACKGROUND: Proton pump inhibitors (PPIs) are a class of medications indicated for the treatment of gastric acid–related diseases. Hypomagnesemia is a rare but serious adverse effect of PPIs. OBJECTIVE: To address the association between the use of different PPIs and hypomagnesemia by examining the frequency of occurrence of hypomagnesemia among the reported adverse drug reactions from the Food and Drug Administration (FDA) Adverse Event Reporting System database. METHODS: We conducted a cross-sectional study of PPI-associated adverse effect cases reported to the FDA between November 1, 1997, and April 1, 2012. Logistic regression was used to examine the association of sex, age, and different PPIs with hypomagnesemia. χ2 Analysis was conducted to investigate the association of PPI-associated hypomagnesemia with hypocalcemia and hypokalemia.RESULTS: Among 66,102 subjects identified as experiencing 1 or more adverse effects while taking a PPI, 1.0% (n = 693) were reported to have hypomagnesemia. The mean (SD) age of PPI users presenting with hypomagnesemia was 64.4 (12.9) years. Results from logistic regression indicated that, compared with esomeprazole, all other PPIs had a higher rate of hypomagnesemia, with pantoprazole having the highest rate (OR 4.3; 95% CI 3.3–5.7; p < 0.001). The risk of female subjects having hypomagnesemia (OR 0.83; 95% CI 0.71–0.97; p = 0.016) was significantly lower than that of males. Elderly subjects (age >65 years) were at increased risk of PPI-associated hypomagnesemia (OR 1.5; 95% CI 1.2–1.7; p < 0.001). χ2 Analysis showed strong association between hypomagnesemia and both hypocalcemia (p < 0.001) and hypokalemia (p < 0.001). CONCLUSIONS: All PPIs were associated with hypomagnesemia, with esomeprazole having the lowest risk and pantoprazole having the highest risk. The risk of PPI-associated hypomagnesemia was higher in males and the elderly population. Hypocalcemia and hypokalemia commonly coexisted with PPI-associated hypomagnesemia.